Hubungan Antara Keaktifan Warga Belajar Dengan Hasil Belajar Pada Mata Pelajaran Matematika Program Paket B di PKBM - Cici Sridestiva Andra; Vevi Sunarti (Jurnal Family Education, 2022)
This research is motivated by the low learning outcomes of residents studying the Package B program at PKBM Tuah Sepakat Nagari Tanjung. It is suspected that this is caused by the lack of active learning of the learning community during the process. The aims of this study were to: 1) to describe the learning activities of the residents in PKBM Tuah Sepakat Nagari Tanjung, 2) to describe the learning outcomes of citizens studying mathematics at PKBM Tuah Sepakat Nagari Tanjung, and 3) to determine the relationship between learning residents and learning outcomes at Mathematics subject package B at PKBM Tuah Agreed Nagari Tanjung. This type of research is quantitative with a correlational approach. The population in this study was the Package B learning community program at PKBM Tuah Sepakat Nagari Tanjung which opened 70 people and the respondents in this study opened 30 people. The results of this study indicate that: 1) the learning activities of the residents in PKBM Tuah Sepakat Nagari Tanjung are still low, 2) the learning outcomes of students learning mathematics in PKBM Tuah Sepakat Nagari Tanjung are still low, and 3) there is a significant relationship between the activeness of the citizens studying with the results studying mathematics in the Package B program at PKBM Tuah Sepakat Nagari Tanjung.